Right to Inclusive Education for Children with Physical Disabilities in Peru: In The Framework of Compliance with International and National Regulations - Seminario-Hurtado, Nuccia (2025)
The main objective of this article is to analyze how the right to inclusive education for children with physical disabilities is guaranteed in Peru within the framework of compliance with international and national regulations. A qualitative method is used, with a descriptive approach and a documentary design.The results show that progress has been made gradually in the development of standards and policies. However, there are still obstacles in society and in schools, such as the lack of public funding, poor infrastructure, limited accessible materials, and the lack of participation and training of teachers. The study concludes that inclusive education is a right of people with disabilities, and for it to be exercised properly, it is not enough for the State to participate; the sensitization of the educational community is also necessary.